Risk Factors and Medico-Economic Effect of Pancreatic Fistula after Pancreaticoduodenectomy - Renping Huang; Bing Liu; Hua Chen; Xuewei Bai; Rui Kong; Gang Wang; Yongwei Wang; Bei Sun; Yinghui Guan (Gastroenterology Research and Practice)
The study aimed to uncover the risk factors for the new defined pancreatic fistula (PF) and clinical related PF (CR-PF) after pancreaticoduodenectomy (PD) surgery and to evaluate the medico-economic effect of patients. A total of 412 patients were classified into two groups according to different criteria, PF and NOPF according to PF occurrence: CR-PF (grades B and C) and NOCR-PF (grade A) based on PF severity. A total of 28 factors were evaluated by univariate and multivariate logistic regression test. Hospital charges and stays of these patients were assessed. The results showed that more hospital stages and charges are needed for patients in PF and CR-PF groups than in NOPF and NOCR-PF groups (P<0.05). The excessive drinking, soft remnant pancreas, preoperative albumin, and intraoperative blood transfusion are risk factors affecting both PF and CR-PF incidence. More professional surgeons can effectively reduce the PF and CR-PF incidence. Patients with PF and CR-PF need more hospital costs and stages than that in NOPF and NOCR-PF groups. It is critical that surgeons know the risk factors related to PF and CR-PF so as to take corresponding therapeutic regimens for each patient.